3 Bernard Bush, Laws of the Royal Colony of New Jersey 15 (1980) - (:unkn) unknown (My University, 1746)
Sought to raise 500 troops for a state army expedition against Canada. This act also made it unlawful for an officer "to inlist any young Men under the Age of Twenty One Years, or any Slaves who are so for Term of Life, bought Servants, or Apprentices, without the Express Leave in Writing of their Parents or Guardians, Masters or Mistresses."
Keywords: ARMED FORCES; MILITIAS